Cho Abelian decomposition of monopole-antimonopole pair gauge potentials - Khai, Ming Wong; Pei, Yen Tan; Rosy, Teh (Universiti Kebangsaan Malaysia, 2013)
Recently we have reported on standard MAP and generalized Jacobi Elliptic monopole-antimonopole pair (MAP) solutions of the SU(2) Yang-Mills-Higgs model. Here we apply Cho Abelian decomposition to the gauge potential of these MAP solutions. It is shown that the point singularities at the locations of the monopole (antimonopole), that comes from the restricted part, are removed by the unrestricted valence potential. We also consider the effect of decomposition upon energy and magnetic charge density for the cases of standard MAP and generalized Jacobi elliptic MAP solutions, under the conditions of vanishing (λ = 0) and non vanishing (λ = 1) Higgs potential.